2016
DOI: 10.3109/07435800.2016.1141937
|View full text |Cite
|
Sign up to set email alerts
|

Modeling vitamin D insufficiency and moderate deficiency in adult mice via dietary cholecalciferol restriction

Abstract: Purpose We sought to develop and characterize a model of human vitamin D nutritional insufficiency/deficiency in the adult mouse, which could have broad utility in examining health consequences of this common condition. Methods Adult mice were fed diets containing cholecalciferol contents of 0.05IU/g, 0.25IU/g, 0.5IU/g or 1.5IU/g for four months. We studied induction of steady-state vitamin D insufficiency, and its consequences on primary cholecalciferol metabolite levels, calcium homeostasis, parathyroid ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
16
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
(17 reference statements)
7
16
1
Order By: Relevance
“…With regards to other serum markers, Belenchia et al reported changes in serum calcium levels in vitamin D deficient mice, which was not observed in this study, our previous study [ 47 ], or by Mallya et al [ 63 ]. Likewise, Belenchia et al was the only study to report significant differences in PTH concentrations; however, intact PTH was trending towards elevation in our vitamin D insufficient mice (p=0.10), and our study may have been insufficiently powered to observe this.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…With regards to other serum markers, Belenchia et al reported changes in serum calcium levels in vitamin D deficient mice, which was not observed in this study, our previous study [ 47 ], or by Mallya et al [ 63 ]. Likewise, Belenchia et al was the only study to report significant differences in PTH concentrations; however, intact PTH was trending towards elevation in our vitamin D insufficient mice (p=0.10), and our study may have been insufficiently powered to observe this.…”
Section: Discussioncontrasting
confidence: 88%
“…Our study also confirms the findings that altering vitamin D supplementation results in a rapid shift (both depletion and repletion) in serum 25-OH vitamin D levels (within 2 weeks) that is sustained relative to the amount of supplementation [ 33 , 47 , 63 ]. Our 12-month study was approximately 6 weeks longer than Belenchia et al [ 33 ], which was performed in female mice, and together these studies demonstrate little to no impact of gender on the relationship between vitamin D supplementation and serum 25-OH vitamin D concentration.…”
Section: Discussionsupporting
confidence: 88%
“…The vitamin D level was adjusted to minimize the contribution of dietary vitamin D to VDR signaling, which might interfere with the effects of LCA. This dose of vitamin D has been previously shown to cause no significant changes in body weight, serum calcium, serum parathyroid hormone, cortical or trabecular bone density, or parathyroid gland morphology, even after 4 months on the diet (86,87). We observed no overt defects in the mice after 3 days on this diet.…”
Section: Mouse Experimentssupporting
confidence: 52%
“…The Ch and Ch-D diets were purchased from Purina Mills LabDiet. Levels of dietary D3 used in deficient diets are high enough to prevent physiologically relevant changes in levels of serum calcium, serum phosphate, or parathyroid hormone ( Anderson et al, 2007 ; Harnack et al, 2011 ; Mallya et al, 2016 ). Animals (for mice and rats, see Table 2 ) used in all treatment studies were maintained on either standard rodent Ch (RMH 3000, Purina Mills LabDiet), the HF diet, or the HF-D diet ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%